Effect of a policy intervention on handset subsidies on the intention to change handsets and households' expenses in mobile telecommunications. Issue 8 (December 2017) - Lee, Changjun; Jung, Sungdo; Kim, Keungoui
Highlights: Policy intervention on handset subsidies lowered users' willingness to switch handsets. The intervention increased spending on households' expenses in handset installment. The intervention has no significant effect on households' expenses in online content. Abstract: This study examined effect of a policy intervention that provides an upper limit for handset subsidies on users' intention to change handset and households' expenses on mobile telecommunications. The Korean government has prohibited mobile network providers from providing excessive subsidies for mobile handsets to attract subscribers since Nov. 2014 according to the mobile act. Using the exogenous variation, we estimate the impact of the policy on the intention to change handsets and expenses on handset installment, total mobile communications, and online content. The longitudinal data are from the 2014 to 2015 waves of the Korea Media Panel Survey. The mobile act lowered the predicted probability of switching handsets by 0.4% points. Moreover, the mobile act increased the predicted probability of any expense on handset installment by 7.5% points and had a significant impact on the amount of expenses on handset installment, with an increase of 7.8%. The mobile act lowered users' willingness to switch handsets and increased spending on handset installment. This increased burden in handset installment might shrink the online content market, which has a large need for government support, as well as decrease consumers' welfare. We assert that the policy intervention on handset subsidies is questionable with regard to both consumer welfare and the healthiness of the ICT ecosystem.